Practical corpus linguistics : an introduction to corpus-based language analysis - Weisser, Martin (Malden, MA : Wiley Blackwell, 2016)
"Introduces a number of easy-to-use, yet powerful, free analysis resources consisting of standalone programs and web interfaces for use with Windows, Mac OS X, and Linux"--
Includes bibliographical references and index.
Keywords: Linguistic analysis (Linguistics) -- Databases; Linguistic analysis (Linguistics) -- Software; Corpora (Linguistics) -- Methodology; Corpora (Linguistics) -- Technological innovations; Computational linguisitics -- Methodology; Computer network resources -- Evaluation; Citation of electronic information resources; LANGUAGE ARTS & DISCIPLINES / Linguistics / General